Informality and formality: Fiscal policy in DSGE model (2014)
We develop a DSGE model of the Colombian economy to assess the effect of tax policy on informal employment and income distribution.The model recreates a small open economy, with persistent income inequality, a substantial degree of informality, and different possibilities of government intervention. This paper evaluates the consequences of government transfer payments to households with lower incomes. We find that although transfer payments have a positive effect on income distribution, financing them requires an adjustment in government finances (cut spending or increase revenue through the use of various taxes), have negative effects on the economic as a whole.